AS RESPONSE TO THE CLAIMS OF GENOCIDE: THE ISSUE OF THE PROTECTION OF RIGHTS OF THE RELOCATED ARMENIANS (URFA EXAMPLE) - Çelik, Ahmet (Arif YILDIZ, 2018)
In 27 May 1915, the relocation law that was introduced under the extraordinary conditions of the First World War and that forced Armenians to migrate has been an issue of distortion with an attempt to show it as genocide. However, there are no events justifying such a claim of genocide as evidenced in the developments during and after the relocation. The Armenian problem that started in Urfa in 1895 had begun to become more and more intense, and there had been many conflicts between Armenians and Muslims in the city. With the decision taken by the Ottoman State in 1915, a large part of the Armenian population in the city was sent to Syria. However, the rights of Armenians who were sent by relocation plan were protected. Based on the Urfa example, this paper aims to prove that the events of 1915 were not genocide, that the conditions of the period caused the events. We base our discussion on the historical records showing the funding to compensate the needs of Armenians and the repairs of the schools and the churches belonging to Armenia. Additionally, the documents show that the rights Armenian people were considered who wanted their goods back.

27 Mayıs 1915 yılında, Birinci Dünya Savaşı’nın olağanüstü şartları içinde çıkarılan Tehcir Kanunu ve Ermenilerin zorunlu olarak göç ettirilmesi, soykırım olarak gösterilmeye çalışılmaktadır. Ancak gerçekleşen olayların soykırımla ilgisi yoktur. Tehcir sırasında ve sonrasındaki gelişmeler bunu ispatlar niteliktedir. Urfa’da 1895 yılında başlayan Ermeni olayları giderek şiddetlenmeye başlamış, bu nedenle şehirde Ermenilerle Müslümanlar arasında çok defa çatışmalar olmuştur. Osmanlı Devleti’nin 1915 yılında almış olduğu bir kararla Ermeni nüfusun Suriye’ye sevk edilmesi plânı çerçevesinde, şehirde bulunan Ermeni nüfusun büyük bir kısmı Suriye’ye gönderilmiştir. Ancak tehcir ile gönderilen Ermenilerin hakları korunmuştur. Çalışmamız; Tehcir Kanunu çerçevesinde gelişen olayların, dini, siyasi veya ırki bir grubu sistemli olarak yok etmek anlamına gelen soykırım olmadığını, şartlara göre alınan önlemler olduğunu göstermek amacıyla, Urfa şehrinde yaşayan Ermenilerin iaşelerinin temini için yapılanlar, burada yaşayan Ermenilere yevmiye verilmesi, Ermenilere ait okul ve kiliselerin tamiri, mallarını geri isteyen Ermeni milletinden kişilerin haklarının gözetilmesi konularına ait belgelerin incelenmesinden oluşmaktadır.
SOYKIRIM İDDİALARINA YANIT OLARAK; TEHCİRE TABİ TUTULAN ERMENİLERİN HUKUKUNUN KORUNMASI MESELESİ (URFA ÖRNEĞİ)